Multidisciplinary Research: Globalizing the Malay Language for the World Stage: (Penyelidikan Multidisiplin: Mensejagatkan Bahasa Melayu di Pentas Dunia) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This article will show how employing the technology of today will enable the Malay language to develop further and remain competitive. A multidisciplinary approach may be able to breathe new life into the field of Malay language studies. An inter-lingual comparative study may widen our understanding of other languages and cultures. The integration of information technology and language studies has led to corpus linguistics. The involvement of the medical field in the study of speech has resulted in speech therapy research. Geographical information system (GIS) tools can be employed in dialect studies. This technology may be used to draw maps, show the distribution of sounds and isoglosses. The dialect geography that is thus created is more accurate and convincing. Such multidisciplinary research may internationalize Malay language research and bring it up to par with those of other languages in the world. All this will lead to an understanding of the globalization of languages in order that our national language continues to be relevant in changing times.Keywords: corpus studies, dialectology, GIS, isoglosses, multidisciplinary research, globalization